1992
DOI: 10.1161/01.res.71.2.346
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial mechanical, biochemical, and structural alterations induced by chronic ethanol ingestion in rats.

Abstract: To determine the effects of moderate ethanol consumption on the mechanical, biochemical, and structural characteristics of the heart, myocardial mechanical performance, contractile protein enzyme activity, and the number and size of myocytes were measured in male Fischer 344 rats after the ingestion of 30%o oral ethanol. Papillary muscles removed from the left ventricle were greater in length, weight, and crosssectional area than the corresponding muscles from the right side. However, no differences were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…36 Structural changes in cardiac muscle were also observed in heavy drinkers 37 as well as in ethanol-fed rats. 38 These changes may be involved in alcohol-induced cardiomyopathy, heart failure and arrhythmia.…”
Section: Cardiac Actionsmentioning
confidence: 99%
“…36 Structural changes in cardiac muscle were also observed in heavy drinkers 37 as well as in ethanol-fed rats. 38 These changes may be involved in alcohol-induced cardiomyopathy, heart failure and arrhythmia.…”
Section: Cardiac Actionsmentioning
confidence: 99%
“…force exerted by diastolic blood pressure (blood pressure in rats is Ϸ19Ϯ2.8/14Ϯ1.6 mN/mm 2 ). The size of the cuff of the cell grafts around the aorta in the present study was approximately the same as a rat papillary muscle, Ϸ8 mm in length with a cross-sectional area of Ϸ1 mm 2 and muscle weight of Ϸ10 mg, 18 which is the equivalent of Ϸ200 000 cardiomyocytes (there are Ϸ20 million cardiomyocytes in 1 g of heart tissue; therefore, 200 000 in 10 mg). The force produced by papillary muscles of rats (more than 20 mN/mm 2 ) 19,20 is considerably greater than that needed to overcome diastolic pressure.…”
Section: Discussionmentioning
confidence: 82%
“…The tension developed by right ventricular myocytes from rats is 39Ϯ2 mN/mm 2 measured in single skinned myocytes, 21 and in one study, developed tension of rat papillary muscles was as high as 60 mN/mm 2 . 18 Therefore, in theory, grafted aortic cardiac cells, once fully matured and connected, should be able to sustain enough force to contract the aorta in diastole. At least 200 000 surviving and functioning cardiomyocytes would be needed around the aorta to contract the aorta in diastole.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its established deteriorating effect on the contractile ability of the heart and cardiomyocytes (Thomas et al, 1994), ethanol causes the death of cardiomyocytes: it has been reported that moderate but chronic (8 months) ethanol consumption results in the loss of ~14% myocytes in the hearts of rats (Capasso et al, 1992). Coincident with these observations, there are many reports showing that the direct exposure of cardiomyocytes to ethanol results in acute apoptotic cell death (Chen et al, 2000;Wang et al, 2015;Noritake et al, 2015).…”
Section: Discussionmentioning
confidence: 97%